Bilingual Competence and the Suppressive Influence of English on Yoruba - Adegbite, Adewale Bandele (2014)
The contact between English and Yoruba, a Nigerian language, is a typical example of the language contact situation that has existed between English and many other Nigerian languages since the middle of the 19th Century. The contact between the languages has yielded some linguistic and sociolinguistic features, which overlap bi-directionally in the contact languages as aspects of linguistic facilitation or interference.